Toxic effect of copper-zinc pyrite ore on erythropoiesis in chronic experiment - K. R. Ziyakaeva; A. F. Kayumova (Сибирский научный медицинский журнал, 2020)
Natural ores contain a large number of harmful components for human health. Workers of mining and processing enterprises, who have long-term contact with these natural elements, are often diagnosed with anemia, that pathogenesis is not sufficiently studied. Aim of the study was to detail the mechanisms of rats’ erythron disorders in the long-termintoxication by natural complex of heavy metal compounds of copper-zinc pyrite ore.Material and methods. The work was performed on 60 white non-linear male rats aged 3-4 months weighing 220,52 ± 15,51 g. The experimental group of animals (n = 40) were injected orally with water suspension of copper-zinc powder in a bread crumb an hour before standard feeding during 75-120 days. The blood and bone marrow of experimental groups of rats were carried out on the 75-th, 90-th, 105-th and 120-th days of the experiment. The blood and bone marrow of rats’ control groups were studied on the 75-th and 105-th day. The central part of erythron was assessed by the number and composition of the erythroblastic islets (EI) of bone marrow, the number of free macrophages, the coefficients of involvement of colonyforming units of red blood cells (CFU-E) and macrophages into erythropoiesis.Results. In the peripheral blood of experimental rats the number of red blood cells and the content of hemoglobin were reliably less than the control values on the 90-th and 120-th day, the number of reticulocytes was exceeded the control group on the 75-th, 105-th and 120-th day. In the bone marrow of experimental rats there were only a single EI1 and EI2 classes of maturity. Throughout the experiment, the content of free macrophages and EI with reticulocytes «crown» in the bone marrow of rats was elevated, and the concentration of iron and erythropoietin in the blood, on the contrary, was reduced. The intensity of CFU-E involvement in the erythropoiesis was less than the control level by 2 times on 105th and 120th days of the experiment.Conclusion. With long-term introduction of copper-zinc pyrite ore in the bone marrow of rats the process of formation of EI de novo is suppressed by destabilizing the contact of free bone macrophages with young red blood cells. There is reduces in the content of serum erythropoietin and bound iron, that combines with the change of erythropoiesis nature, leads to decreasing of the number of mature red blood cells and content of hemoglobin in the peripheral blood.